A history of apprenticeship nurse training in Ireland - Fealy, Gerard M. (Routledge studies in nursing history., 2006)
Based on new research using previously unpublished sources, this compelling text is an in-depth study of the history of nurse education in Ireland, presenting a new authoritative account of the history of the traditional system of training in Ireland. Introduced as part of the reforms of hospital nursing in the late nineteenth century, apprenticeship nurse training was a vocational extension of secondary education. Residing outside the mainstream of higher educational provision it provided nurses with the knowledge and technical skills for sick nursing, whilst also functioning to soc.